2019
DOI: 10.1177/0899764019859435
|View full text |Cite
|
Sign up to set email alerts
|

Does Government Funding Make Nonprofits Administratively Inefficient? Revisiting the Link

Abstract: There is widespread concern that government funding bureaucratizes nonprofits and causes them to be administratively inefficient. This study brings together contrasting streams of literature and hypothesizes a curvilinear relationship between government funding and nonprofits’ administrative efficiency. Using a longitudinal dataset of U.S. Agency for International Development (USAID)-registered nonprofits, we find evidence for this nonlinear effect. In particular, as the proportion of a nonprofit’s government … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…Finalmente, la creciente función del sector en los sistemas de bienestar parece ir de la mano de una creciente dependencia de la financiación pública, lo que, siguiendo a Lu & Zhao (2019) plantea al menos dos retos gerenciales: en primer lugar, como asegurar financiación pública estable, tanto para las grandes entidades como para las pequeñas; y por el otro, cómo gestionar la dependencia que esto genera. En definitiva, avanzar tanto en el papel de agente social de las entidades podría potenciar las que son identificadas como dos de las principales funciones del sector: continuar siendo intermediarias y representantes de las necesidades de los sectores más vulnerables, y apoyar y complementar la acción pública para desarrollar un sistema de atención lo más completo y profesionalizado posible.…”
Section: Discussionunclassified
“…Finalmente, la creciente función del sector en los sistemas de bienestar parece ir de la mano de una creciente dependencia de la financiación pública, lo que, siguiendo a Lu & Zhao (2019) plantea al menos dos retos gerenciales: en primer lugar, como asegurar financiación pública estable, tanto para las grandes entidades como para las pequeñas; y por el otro, cómo gestionar la dependencia que esto genera. En definitiva, avanzar tanto en el papel de agente social de las entidades podría potenciar las que son identificadas como dos de las principales funciones del sector: continuar siendo intermediarias y representantes de las necesidades de los sectores más vulnerables, y apoyar y complementar la acción pública para desarrollar un sistema de atención lo más completo y profesionalizado posible.…”
Section: Discussionunclassified
“…Conversely, Ecer et al's (2017) much larger US study of 97,040 Form 990 4 returns for 2003 found larger charities more efficient on the same measure. They noted a relationship between fundraising source and efficiency, as did Lu and Zhao (2019), conducting content analysis of 704 organisations' financial statements filed with the US Agency for International Development (US AID) (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014). They identified a curvilinear relationship: voluntary organisations' 'operating efficiency' (as indicated by low administrative expenses) could occur with low or high levels of government funding.…”
Section: Quantitative Analysis Of Publicly Available Financial Data As a Proxy For Performancementioning
confidence: 93%
“…For example, Lu (2015) showed that a greater bureaucratic tendency, domain consensus with the government, and longer funding history, increase government funding. Lu and Zhao (2019) found an inverted U-shaped relationship between government funding and NFP administrative efficiency. The conventional concern that government funding hurts NFPs' administrative efficiency (as NFPs need to devote substantial resources to fulfill the funding requirements) receives limited support from this study.…”
Section: Donationsmentioning
confidence: 96%